The NISER econometric model of the Nigerian economy analysis of model and results: interim report - Owosekun Akinola A. ([Ibadan] Niser, 1984)
The NISER econometric model of the Nigerian economy comprises seven blocks namely, production, balance of payments, demand, foreign trade, employment, price and money.
Includes bibliographical reference
osa 26/2/2019
Loans